2010
DOI: 10.21273/jashs.135.3.230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SAG12-ipt and HSP18.2-ipt Expression on Cytokinin Production, Root Growth, and Leaf Senescence in Creeping Bentgrass Exposed to Drought Stress

Abstract: Drought stress is a widespread abiotic stress that causes a decline in plant growth. Drought injury symptoms have been associated with an inhibition in cytokinin (CK) synthesis. The objectives of this study were to investigate whether expression of a gene (ipt) encoding the enzyme adenine isopentenyl phosphotransferase for CK synthesis ligated to a senescence-activated promoter (SAG12) or a heat shock promoter (HSP18.2) wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 54 publications
5
72
2
Order By: Relevance
“…It has been reported that drought stress can lead to an increase in ABA level of creeping bentgrass (DaCosta and Huang 2007a, b). We noticed that drought stress resulted in an ABA increase in both treatments, while exogenous Spd pretreatment almost had no effect on ABA accumulation in creeping bentgrass with significant change of endogenous PA. Merewitz et al (2010) reported that cytokinin regulate drought tolerance of creeping bentgrass through changing the balance of ABA, rather than accumulating more ABA. As a drought resistant bentgrass, velvet bentgrass exhibited significantly less ABA accumulation than creeping bentgrass, which could allow continued gas exchange and sustained plant survival during drought stress (DaCosta and Huang 2007a, b).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that drought stress can lead to an increase in ABA level of creeping bentgrass (DaCosta and Huang 2007a, b). We noticed that drought stress resulted in an ABA increase in both treatments, while exogenous Spd pretreatment almost had no effect on ABA accumulation in creeping bentgrass with significant change of endogenous PA. Merewitz et al (2010) reported that cytokinin regulate drought tolerance of creeping bentgrass through changing the balance of ABA, rather than accumulating more ABA. As a drought resistant bentgrass, velvet bentgrass exhibited significantly less ABA accumulation than creeping bentgrass, which could allow continued gas exchange and sustained plant survival during drought stress (DaCosta and Huang 2007a, b).…”
Section: Discussionmentioning
confidence: 99%
“…The ipt gene was cloned from agrobacterium ( Agrobacterium tumefaciens ) and SAG12-ipt plants were transformed using the Agrobacterium method as described previously [24, 19–20]. In order for ease of comparison to previous results, the same plant material used for proteomic and metabolomic evaluation [34] was used for SSH analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Gene sequences were categorized based on their predicted function based on the system used previously in Bevan et al . [23] and [23]. Sequences were evaluated to remove redundant base pairs and vector sequences manually and through use of VecScreen BLAST database.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly cytokinins are known to delay leaf senescence as shown in experiments that prolonged the life span of leaves when the cytokinin biosynthetic IPT gene was expressed under the control of a senescence-specific promoter SAG12 (Gan and Amasino 1995) or a heat-shock promoter HSP18.2 (Merewitz et al 2010). Identification of an AHK3 gain-of-function mutant, ore12-1, revealed that AHK3, not AHK2 or AHK4, is the primary cytokinin receptor functionally regulating leaf senescence via an ARR2-specific phosphorelay cascade (Kim et al 2006).…”
Section: Senescence and Leaf Longevity: Receptors For Going Greenmentioning
confidence: 99%